The JuxtaLearn Process in the learning of Maths’ Tricky Topics: practices, results and teacher’s perceptions - Cruz, Sara Maria Alves (2017)
This paper presents a study developed in the framework of a training course for teachers of STEM areas on the JuxtaLearn process. This process, divided into eight steps, aims to improve student understanding of threshold concepts by planning, editing and sharing creative videos in CLIPIT. CLIPIT is an online platform for collaborative learning designed to support the JuxtaLearn process. We describe the training of eight teachers, and the subsequent supervision of one of them, a math teacher, made to understand how the JuxtaLearn process was applied with her students. We collect qualitative data through the observation of the teacher's work. Also, quantitative data through initial and final quizzes applied to the students, to understand their level of understanding of the tricky topic, automatic records on CLIPIT and a satisfaction questionnaire applied to the eight teachers to assess the ease of use with the CLIPIT. The results show that teachers were able to put into practice the eight steps of the JuxtaLearn process and suggest that students’ engagement in creating creative videos helped them in overcoming tricky math topics.